(3eHGOF GdGbJUGO (B/s - (3Meh, YGQas; (3CHh TQGQ, Ydj s ((3YeGf(B: s (3OGQ GHf QTO ddfTQ(B, s)
(3eONd YGe ddEbJUGO, YfGUQ GdEfJGL, GdWdH hGdYQV, JMOjO GdCKeGf, GdESJgdGc hGdESJKeGQ, GdEfaGb GdMchej, GdONd Gdbhej hGdfGJL Gdbhej, GdCLhQ hGdHWGdI hGdJVNe, GdSjGSGJ GdfbOjI hGdeGdjIs
(3HHdhZQGajG U(B.140s
Keywords: (3GdGbJUGOs; (3GdGbJUGO cdjs; (3GdEfJGLs